Ambiguitas Pemaknaan Pesan Sebagai Komodifikasi dalam Personality Peformance Multikultural Pada Sosok Soimah - Kheyene Molekandella Boer (Program Studi Ilmu Komunikasi, 2013)
The intense competition between private television in Indonesia force the television workers to rise their effort in order to still competitive. The implication is private television should make a program that could give high ratings. It means, television workers treat their programme as a commodification. One example of commodification by Indonesian private television is the presence of Soimah. Soimah is being performed as Javanese traditional woman. But in her performance, Soimah act as Javanese woman that have oral competence –the things that contrary with the Javanese culture. In Javanese culture, woman should polite, kind, and elegant.This article assumed media representation could create cultural ambiguity message and shared meaning process that could be misinterpret by the audience. The image of Javanese woman could distort. Here, commodification victimizes the cultural element. This article discuss about representation in Soimah’s personality performance in television.